Smoking and liver cancer in China: case-control comparison of 36,000 liver cancer deaths vs. 17,000 cirrhosis deaths. - Chen, Z; Liu, B; Boreham, J; Wu, Y; Chen, J; Peto, R (2003)
Liver cancer and liver cirrhosis are common causes of death in China, where chronic lifelong hepatitis B infection is a major cause of both diseases. To help determine whether smoking is a cofactor for the development of liver cancer, we ascertained retrospectively the smoking habits of 36,000 adults who had died from liver cancer (cases) and 17,000 who had died from cirrhosis (controls) in 24 Chinese cities and 74 rural counties. Calculations of the smoker vs. nonsmoker risk ratios (RR) for liver cancer mortality were standardised for age and locality. Among adult men (aged 35+) there was a 36% excess risk of death from liver cancer among smokers (smoker vs. nonsmoker standardised risk ratio [RR] =1.36, with 95% confidence interval [CI] 1.29-1.43, 2p<0.00001; attributable fraction 18%). In the general male population this indicates absolute risks of death from liver cancer before age 70 of about 4% in smokers and 3% in nonsmokers (in the absence of other causes). Most liver cancer, however, occurs among the 10-12% of men with haematological evidence of chronic hepatitis B infection, so among them the corresponding risks would be about 33% in smokers and 25% in nonsmokers. The RR was approximately independent of age, was similar in urban and rural areas, was not significantly related to the age when smoking started but was significantly (p<0.001) greater for cigarette smokers than for smokers of other forms of tobacco. Among men who smoked only cigarettes, the RR was significantly (p<0.001 for trend) related to daily consumption, with a greater hazard among those who smoked 20/day (RR 1.50, 95% CI 1.39-1.62) than among those who smoked fewer (mean 10/day: RR=1.32, 95% CI 1.23-1.41). Smoking was also associated with a significant excess of liver cancer death in women (RR 1.17, 95% CI 1.06-1.29, 2p=0.003; attributable fraction 3%), but fewer women (17%) than men (62%) were smokers, and their cigarette consumption per smoker was lower. Among women who smoked only cigarettes, there was a significantly greater hazard among those who smoked at least 20/day (mean 22/day: RR=1.45, 95% CI 1.18-1.79) than among those who smoked fewer (mean 8/day: RR=1.09, 95% CI 0.94-1.25). These associations indicate that tobacco is currently responsible for about 50,000 liver cancer deaths each year in China, chiefly among men with chronic HBV infection.